Women and family governance in the hospitality industry. A study of medium-sized firms in the three most attractive Italian regions - Tognazzo, Alessandra; Gubitta, Paolo (Piccola Impresa / Small Business, 2023)
Purpose: Given the relevance of small and medium businesses and family influence in the hospitality industry and its importance for the Italian economy, we aim to examine the relationship among women in governance, family firm governance, and firm performance. Design/methodology/approach: We focus on medium-sized hospitality firms located in the three most touristic Italian regions, namely Lombardy, Veneto, and Lazio. Findings: In short, our evidence suggests that family-governed companies are a context where the representation of females in the governance system is supported and effective.